INTERNATIONAL SYMPOSIUM AT MONTPELLIER - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
international symposium on Systems oriented research in agriculture and rural development was held in Montpellier, France, in November 1994